O ritual de visitação ao cemitério, sentidos e significados: um estudo qualitativo na região Sul do Brasil - Ritter, Janete Maria (2016)
The rituals are present in many phases of the human life s transition; it is not different in the transition of life to death. Referring to death, men have been modifying in their way of relating with it, mainly when the issue is taking care and burying their dead people. The objective of this research is to understand the meaning of visits to the cemetery where people have their beloved ones buried. This research is about a qualitative study with nine participants that have lost someone close to them. The number of participants was reached by the sample saturation standard. Semi directed interviews and campus observations were made and analyzed. The results show that the visits awake many feelings, such as the possibility to understand the caring after death, or even guilt when the visits cannot be made for some reason. There is a belief in the existence of communication between the living and the death worlds and in the cemetery place as a local to understand life through the evocation of memories and regards. It was also observed that the Park Cemetery place is seen as a space that is not thought as a cemetery, by reflecting the beauty and the life, not realizing death. However, the traditional cemetery is seen as a heavy place that refers to death. Such results evidenced how much practicality, beauty and security are exceled in contemporaneity, highlighting the increasing outsourcing of the caring through the mortuary business. Besides that, it is possible to conclude that society banes death and that how new spaces and services have been corresponding and consolidating this social request. Therefore, it is necessary that people reflect more about death rituals, highlighting the Psychology area which needs publications about this issue.